Retroperitoneal Appendicitis around the Ureter: A Rare Case Reports - Wang, Jun; Dai, Feng; Liu, Xiaoming; Ju, Wen; Liang, Huageng; Zhang, Xiaoping (Archives of Clinical and Medical Case Reports, 2022)
Some appendicitis with the appendix in rare localization shows atypical presentations, leading to diagnostic difficulties. We firstly report one case of retroperitoneal appendicitis encroaching on the ureter. The diagnosis was interpreted as ureter cancer by the MRU (Magnetic Resonance Urography) and PET (Positron Emission Computed Tomography), whereas the intraoperative finding and pathological examination finally confirmed that the hydronephrosis was caused by the retroperitoneal appendicitis. Herein, the case report we presented will provide a demonstration for the subsequent differential diagnosis of ectopic appendicitis.